MENELAAH MAKNA KONTEMPLASI MARIA DALAM LUKAS 2:15- 20 DAN RELEVANSINYA BAGI KEHIDUPAN CALON IMAM - Gerardus Taena; Mario S. Bahi; Antonius B. M. H. Etoehaq; Angelus G. B. Sallu (STIPAS Keuskupan Agung Kupang, 2026)
This article examines the meaning of Mary’s contemplation from the perspective of Luke 2:15–20. This passage describes Mary’s response after hearing the shepherds’ testimony regarding the birth of Jesus. The Gospel records that Mary “treasured all these things in her heart and pondered them.” This expression reveals Mary’s profound inner attitude in responding to the salvific events that had taken place. Mary’s contemplation was not merely a matter of recalling the events she had experienced, but also a process of faith-filled reflection to understand God’s work in her life. Through this attitude, Mary emerges as a person open to divine mystery and capable of processing her life experiences in the light of faith. This study aims to explore the deepest meaning of Mary’s attitude of treasuring and pondering all these things in her heart. The focus of the study is to understand how Mary’s contemplative attitude can be interpreted as a model of spirituality relevant to the spiritual life, particularly for seminarians. Contemplation is understood as an inner process that helps a person discern God’s presence and work in the events of daily life. The method used in this study is library research, which involves examining various theological, biblical, and spiritual sources related to the Gospel of Luke and the concept of contemplation within the Church’s tradition. This approach helps the researcher understand the theological significance of Mary’s attitude while connecting it to spiritual life. The research findings indicate that Mary’s attitude of treasuring and pondering all things in her heart can serve as a model of contemplation for seminarians. This attitude guides them to deeply integrate life experiences, prayer, and ministry into the process of spiritual formation at the seminary.